Carbocatalysis in Liquid‐Phase Reactions. Issue 4 (7th December 2016) - Su, Dang Sheng; Wen, Guodong; Wu, Shuchang; Peng, Feng; Schlögl, Robert
Abstract: There is broad interest in metal‐free catalysis for sustainable chemistry. Carbocatalysis is a "green" option for catalytic transformations in the gas phase as well as in the liquid phase. This is evident by the numerous reports on gas‐phase dehydrogenation and selective oxidation where carbon can be used as a successful alternative to metal oxide systems. Carbocatalysis for liquid‐phase reactions, especially for organic synthesis, is an emerging research discipline and has undergone rapid development in recent years. This Review provides a critical analysis on the state‐of‐the‐art of carbocatalysts for liquid‐phase reactions, with a focus on the underlying mechanisms as well as the advantages and limitations of metal‐free carbocatalysts. Abstract : Carbon as catalyst : Carbocatalysis for liquid‐phase reactions, especially for organic synthesis, has undergone a rapid development in recent years. This Review gives a critical analysis on the state‐of‐the‐art of this area, with a focus on the possible underlying mechanisms as well as advantages and limitations.